High activity and specificity of bacteriophage cocktails against carbapenem-resistant Klebsiella pneumoniae belonging to the high-risk clones CG258 and ST307 - Tellez-Carrasquilla, Sara; Salazar-Ospina, Lorena; Jiménez, J. Natalia (Frontiers in Microbiology, 2024)
IntroductionThe widespread clinical and environmental dissemination of successful clones of carbapenem-resistant Klebsiella pneumoniae (CRKP) represents a serious global public health threat. In this context, lytic bacteriophages have emerged as a promising alternative for controlling these pathogens. This study describes the biological, structural, and genomic characteristics of lytic bacteriophages against the high-risk CRKP clones CG258 and ST307 and describes their performance in combination.MethodsAn experimental study was carried out. Bacteriophages were isolated from hospital wastewater and from wastewater treatment plants (WWTP). Bacteriophages were isolated using the double layer agar technique and their characterization included host range (individual and cocktail), plating efficiency (EOP), infection or bacterial killing curve, one-step curve, bacteriophage stability at pH and temperature conditions, transmission electron microscopy (TEM) and whole genome sequencing.ResultsAfter purification, five active bacteriophages against CRKP were obtained, three bacteriophages (FKP3, FKP4 and FKP14) had targeted activities against CG258 CRKP and two (FKP10 and FKP12) against ST307 isolates. Seven cocktails were prepared, of which Cocktail 2, made up of the bacteriophages FKP3, FKP10, and FKP14, showed the best activity against 85.7% (n = 36/42) of CRKP isolates belonging to both clones, CG258 (80.8%; n = 21/26) and ST307 (93.8%, n = 15/16). The efficiency of the plating (EOP), infection curve, and one-step growth curve showed that the cocktail phages efficiently infected other CRKP isolates (EOP ≥ 0.5), controlled bacterial growth up to 73.5%, and had short latency periods, respectively, (5–10 min). In addition, they were stable at temperatures between 4°C and 50°C and pH between 4 and 10. All bacteriophages belonged to the Caudoviricetes class, and no genes associated with virulence factors or antibiotic resistance were detected.ConclusionThese findings showed bacteriophages and phage cocktails with high specificity against CRKP belonging to the successful clones CG258 and ST307 with promising characteristics, making them an alternative for controlling these clones in different environmental or health settings, biocontrol agents, or disinfectants in industry and in the field of diagnosis.